Ground to Cloud Lightning Flash Currents and Electric Fields: Interaction with Aircraft and Production of Ionosphere Sprites. (3rd August 2014) - Hoole, P. R. P.; Thirukumaran, S.; Ramiah, Harikrishnan; Kanesan, Jeevan; Hoole, S. R. H.
Abstract : This paper presents for the first time a case for the importance of ground to cloud (upward leader) lightning flash parameters for safety testing of direct aircraft-lightning interaction and protection of wind turbines, as well as the importance of radiated electric fields for indirect lightning-aircraft interaction and generation of electric discharges called sprites and halos in the ionosphere. By using an electric circuit model of the transverse magnetic waves along the return stroke channel, electric currents at ground level as well as cloud level are determined for both the cloud to ground lightning flash and the ground to cloud lightning flash. We show that when an aircraft triggers lightning, the electric currents will be much more severe in current magnitude, rate of rise of currents, and frequency spectrum than otherwise and are more severe than the parameters observed for the usual and well monitored (and measured) cloud to ground (downward leader) flashes. The rate of rise of currents and the frequency spectrum of the ground to cloud lightning flash are also given here. The electric fields radiated by the lightning flashes that would appear in the ionosphere are presented for both the earth flash and the ground to cloud flash.